2017
DOI: 10.3389/fphys.2017.00388
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Level Integration of Environmentally Perturbed Internal Phenotypes Reveals Key Points of Connectivity between Them

Abstract: The genotype and external phenotype of organisms are linked by so-called internal phenotypes which are influenced by environmental conditions. In this study, we used five existing -omics datasets representing five different layers of internal phenotypes, which were simultaneously measured in dietarily perturbed mice. We performed 10 pair-wise correlation analyses verified with a null model built from randomized data. Subsequently, the inferred networks were merged and literature mined for co-occurrences of ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
(55 reference statements)
0
4
0
Order By: Relevance
“…Furthermore, the C3 gene is known to have an antimicrobial activity [ 58 ]. In mice it has already been described that genes involved in the complement system respond to different (oral) challenges, i.e., dietary, drug, or immune [ 59 ]. Consequently the complement pathway functioning changes by increased expression of genes C2 , C3 , C4 , CD55 , and factor H, which may be needed as an early defence mechanism against dysbiosis/infection or a dysfunctional barrier [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the C3 gene is known to have an antimicrobial activity [ 58 ]. In mice it has already been described that genes involved in the complement system respond to different (oral) challenges, i.e., dietary, drug, or immune [ 59 ]. Consequently the complement pathway functioning changes by increased expression of genes C2 , C3 , C4 , CD55 , and factor H, which may be needed as an early defence mechanism against dysbiosis/infection or a dysfunctional barrier [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…In mice it has already been described that genes involved in the complement system respond to different (oral) challenges, i.e., dietary, drug, or immune [ 59 ]. Consequently the complement pathway functioning changes by increased expression of genes C2 , C3 , C4 , CD55 , and factor H, which may be needed as an early defence mechanism against dysbiosis/infection or a dysfunctional barrier [ 59 ]. In addition, the gene encoding for MT1A belongs to the metallothionein gene family, which has a high content of cysteine residues that can bind various heavy metals, including zinc.…”
Section: Discussionmentioning
confidence: 99%
“…Examples in reference animals such as mice show the possibilities at this stage. Excellent examples are the studies of Orozco et al [ 18 ] and Benis et al [ 162 ], both using mice as sources of experimental data. In a highly interesting study, Orozco et al [ 18 ] showed how the genotype affected some part of the methylome, while other parts were environmentally affected, how the profiles of gene expression were regulated at the RNA and proteome levels and how the metabolome profile reacted.…”
Section: The Biology Of Complex Traitsmentioning
confidence: 99%
“…In a highly interesting study, Orozco et al [ 18 ] showed how the genotype affected some part of the methylome, while other parts were environmentally affected, how the profiles of gene expression were regulated at the RNA and proteome levels and how the metabolome profile reacted. Benis et al [ 162 ] showed the integration of five biological levels: microbiota, transcriptomics, cytokine and metabolomics in serum and urine, pointing towards several connections between the layers and within the layers. This clearly shows the power of such studies for understanding complex traits by linking the genotype and several phenome levels to the external complex trait phenotype.…”
Section: The Biology Of Complex Traitsmentioning
confidence: 99%